PENGARUH PENGGUNAAN HYPNOTEACHING TERHADAP PENGENALAN BILANGAN ANAK 5-6 TAHUN DI RA BAITUL JUMAâ€™AH - Supardi, Yuniarti Bt; Marmawi, Marmawi; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research is to know the effect of using hypnoteaching method in introducing numbers to 5-6 years old children at Ra Baitul Jumaat, West Pontianak. This research used a quantitative approach and pre-experimental design in form of one-shot case study. The samples are B1 and B2 class consisted of 20 children aged 5-6 years old and also the teacher of B1 and B2 class. The technique of data collection are observation and documentaion. The technique of data analysisÂ is observing the results of research before and after using the method. The data is presented by product moment, a technique to find the correlation between two variables. Based on data analyzing of the effect of using hypnoteaching method in introducing numbers to 5-6 years old children compared to the results of the difference between using conventional methods with the hypnoteaching method, the calculation of the correlation coefficient obtained r count 0.29 in B1 and 0.34 in B2 with a significant level 5% and N = 10 is 0.632 or r table. The hypothesis of this research is if r count < r table then Ho accepted and Ha rejected. Regarding to the correlation coefficient calculation, it was found that the effect of introducting numbers before and after using the hypnoteaching method is categorized as â€œvery lowâ€.Â Keyword : Hypnoteaching Method, The Introduction of Numbers